Real-Time Smart System for Complaint Information System in Campus: Code of Conduct and Infrastructure - Mr. Musawarman; Halimil Fathi; Ricak Agus Setiawan (Journal of Information Technology and Its Utilization, 2024)
In today's competitive business environment, maintaining high levels of customer satisfaction is crucial for the success of any organization. To effectively address customer complaints and concerns, businesses are increasingly relying on digital solutions such as complaint reporting systems. This paper presents the development of an online complaint reporting system designed to streamline the process of receiving, managing, and resolving customer complaints. The system incorporates features such as user-friendly interfaces, secure data storage, automated notifications, and real-time reporting functionalities. Through the implementation of this system, businesses can enhance their customer feedback management processes, improve customer satisfaction levels, and ultimately, strengthen customer relationships. Real-time reporting functionalities provide businesses with valuable insights into trending issues and customer pain points, allowing them to proactively address recurring problems and improve their products and services. By leveraging the online complaint reporting system, organizations can effectively capture, analyze, and respond to customer feedback in a timely manner, enhancing overall service quality and customer satisfaction. In conclusion, the development of an online complaint reporting system represents a significant step towards improving customer feedback management practices. By implementing this system, organizations can establish a more transparent and customer-centric approach to handling complaints, leading to enhanced customer loyalty and positive brand perception.